Influence Factors, Impact and Interventions for Speech Delay and Language Delay in Early Childhood : Systematic Review - Palipung, Rizky Yuniarti; Sintia Paramita; Ni'matuzahroh, (International Journal of Scientific Research and Management (IJSRM), 2024)
Speech delay occurs when a child is unable to produce words correctly or fluently. Whereas language delay occurs when the child has difficulty in understanding what others are saying or difficulty in conveying information and thoughts. Speech delay and language delay allow children to experience several adverse effects such as developmental delays, decreased cognitive, social and emotional abilities, and risk of having poor health status. The literature search used two databases, Scopus and Scholar. Only studies describing influencing factors and interventions on speech and language delay were included. The results of this systematic review suggest that factors influencing the occurrence of speech and language delay in children, generally occur due to the influence of family factors with a history of speech delay and language delay, and gender factors. As well as, interventions that parents and prospective parents can do to avoid the occurrence of speech and language delays in children include, among others, conducting early examinations or early stage early identification to assess child growth, increasing maternal knowledge related to child development education, involving children in reading and activities together, and it is advisable for mothers to conduct routine examinations during pregnancy.